Effect of Tutee Performance on Tutor's Verbal and Nonverbal Behavior. Technical Report No. 305 - Feldman, Robert S.; Allen, Vernon L.; Wisconsin Univ., Madison. Research and Development Center for Cognitive Learning ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The verbal and nonverbal behavior of sixth-grade children tutoring third-grade children was analyzed. The behavior of a sixth grade tutor in a short tutoring session was videotaped. To control the performance of the tutee, a confederate was used who acted in a predetermined manner; the tutee's performance was made to appear either very successful or very poor. It was expected that the performance of the learner would be reflected in both verbal and nonverbal behavior. Results showed that when the student was doing well there was a greater proportion of positively-toned affective statements made by the tutor, and when the student was doing poorly there were more negatively-toned affective statements. Likewise, the nonverbal behavior of tutors tended to reflect the student's performance. The relationship between verbal and nonverbal behavior also was examined. (Author/PD)
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Contract Number: NE-C-00-3-0065.
ERIC Note: Report from the Project on Conditions of School Learning and Instructional Strategies.
Educational level discussed: Elementary Education.
Educational level discussed: Grade 3.
Educational level discussed: Grade 6.
Keywords: Elementary Education; Elementary School Students; Grade 3.; Grade 6.; Nonverbal Communication; Peer Teaching; Task Performance; Tutoring; Verbal Communication; Reports, Research